2020
DOI: 10.3390/app10176131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Greenshell Mussel (Perna canaliculus) Intake on Pathological Markers of Multiple Phenotypes of Osteoarthritis in Rats

Abstract: The prevalence of metabolic osteoarthritis has been increasing worldwide, particularly among women. The aim of this study was to investigate the effects of the New Zealand greenshell mussel (Perna canaliculus; GSM) on osteoarthritis (OA) prevention in a rat model. One-hundred-and-eight female rats aged 12 weeks were divided into four test groups, containing 24 rats each, plus an additional control group. Each test group received one of the four experimental diets: normal control diet (ND), normal control diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The data are consistent with the literature, where a P. canaliculus diet affects visceral fat in rodents (Loehfelm et al., 2020). In addition, the LDL‐C level was significantly reduced in the group with the highest level of P. canaliculus in the diet, thus indicating a reduction in the inflammatory response in several chronic and acute inflammatory disorders such as atherosclerosis, as shown in previous studies (Cetin et al., 2020; Singh et al., 2008; Siriarchavatana et al., 2020; Whitehouse et al., 1997).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The data are consistent with the literature, where a P. canaliculus diet affects visceral fat in rodents (Loehfelm et al., 2020). In addition, the LDL‐C level was significantly reduced in the group with the highest level of P. canaliculus in the diet, thus indicating a reduction in the inflammatory response in several chronic and acute inflammatory disorders such as atherosclerosis, as shown in previous studies (Cetin et al., 2020; Singh et al., 2008; Siriarchavatana et al., 2020; Whitehouse et al., 1997).…”
Section: Discussionsupporting
confidence: 64%
“…The biochemical markers of the renal functions showed that kidney function was not affected by increasing the amount of diet, where creatinine levels were comparable to the control group. Indeed, the BUN/creatinine ratio suggested pre‐renal uremia, which pointed to be associated with a high protein intake, as shown in the literature (Siriarchavatana et al., 2020).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…( 47 ) There was a significant increase of interscapular brown fat due to feeding HFHS diet, but this effect was not present in OVX rats. This conflicting data may not be due to the sole effect of estrogen deficiency but rather combined effects of the hormone and HFHS diet resulting in severely impaired insulin sensitivity, which was revealed by significantly increased HbA1c in the OVX rats fed HFHS diet in our previous report ( 48 ) and which influenced brown fat mass. Similar results of decreased brown fat mass were also revealed in obese male rats with insulin resistance.…”
Section: Discussionmentioning
confidence: 81%
“…This model has been frequently used in obesity research as the convenience of the protocol and representing the public health problem. The surgical model using ovariectomy in female subjects can mimic the menopause condition in women as estrogen loss induces increased food consumption at the transitional period (Siriarchavatana et al, 2022) and worsens metabolic and lipid profiles (Siriarchavatana et al, 2020;Abshirini et al, 2021). Boonyapakorn et al (2019) demonstrated that lacks of testosterone in castrated dogs resulted in significant weight gain due to the reduction of physical activities but this manipulation did not affect metabolic profiles or cardiac function.…”
Section: Discussionmentioning
confidence: 99%